Rationale, design and initial results of an educational intervention to improve provider-initiated HIV testing in primary care. (26th December 2020) - Bogers, Saskia J; Schim van der Loeff, Maarten F; van Dijk, Nynke; Groen, Karlijn; Groot Bruinderink, Marije L; de Bree, Godelieve J; Reiss, Peter; Geerlings, Suzanne E; van Bergen, Jan E A M
Abstract: Objectives: In the Netherlands, general practitioners (GPs) perform two-thirds of sexually transmitted infection (STI) consultations and diagnose one-third of HIV infections. GPs are, therefore, a key group to target to improve provider-initiated HIV testing. We describe the design and implementation of an educational intervention to improve HIV testing by Amsterdam GPs and explore trends in GPs' testing behaviour. Methods: Interactive sessions on HIV and STI using graphical audit and feedback started in 2015. Participating GPs developed improvement plans that were evaluated in follow-up sessions. Laboratory data on STI testing by Amsterdam GPs from 2011 to 2017 were collected for graphical audit and feedback and effect evaluation. The primary outcome was the HIV testing rate: number of HIV tests per 10 000 person-years (PY). Secondary endpoints were chlamydia and gonorrhoea testing rates and HIV positivity ratios. Results: Since 2015, 41% of GPs participated. HIV testing rate declined from 2011 to 2014 (from 175 to 116 per 10 000 PY), more in women than men (176 to 101 versus 173 to 132), and stabilized from 2015 to 2017. The HIV positivity ratio declined from 0.8% in 2011 to 0.5% in 2017. From 2011 to 2017, chlamydia and gonorrhoea testing rates declined in women (from 618 to 477 per 10 000 PY) but remained stable in men (from 270 to 278). Conclusions: The stabilization of the downward trend in HIV testing coincided with this educational intervention. Follow-up data are needed to formally assess the intervention's impact on GP testing behaviour whilst considering contextual factors and secular trends.